Mineral Composition of Selected Honeys From Turkey - KOLAYLI, SEVGI; KONGUR, NAZLI; GUNDOGDU, ALI; KEMER, BARIS; DURAN, CELAL; ALIYAZICIOGLU, REZZAN (Asian Journal of Chemistry, 2010)
The aim of the present study was to determine the levels of some minerals, such as Na, K, Ca Fe, Cu, Zn, Mn, Cr, Pb, in honey samples produced and consumed abundantly in Black sea region of Turkey. Three different floral and authentic honey samples, Anzer (n = 6), Bayburt (n = 8) and chestnut honeys (n = 15) were obtained from Black sea region of Turkey and analyzed by flame atomic absorption spectrophotometer (F-AAS). Both of the Anzer and Bayburt honeys are heterofloral and produced from a largest variety of mountain flowers in Anzer plateau near Ikizdere-Rize and Bayburt plateau, in the East- Black sea region of Turkey, respectively. Third group of monofloral botanical origin chestnut honey samples were supplied from Zonguldak in West Black sea region of Turkey. All samples were analyzed after nitric acid digestion. Nine minerals (Na, K, Ca, Fe, Cu, Zn, Mn, Cr, Pb) were quantified for each honey sample. Iron, copper, zinc, manganese, calcium, chromium and lead were determined by atomic absorption spectrophotometer and potassium, sodium by flame photometer. Na, K, Ca, Fe, Cu, Zn and Mn contents of minerals in honey samples were in the range of 28-41, 564-5007, 173-481, 3.2-6.7, 1.2-2.2, 1.2-17.2 and 1.2-17.2 μg g-1, respectively. However, Cr and Pb were below detection limit (0.01 μg g-1) of the flame AAS. The amounts of K, Na and Ca were the most abundant elements in tested honey samples. Anzer honey samples were high in iron and chestnut samples were in manganese. The results showed that mineral contents in the studied 29 honey samples are highly variable and depend on their geographical and botanical origin.